Microwave transmission through high-temperature superconducting waveguides - Yassin, G; Barboy, I; Dikovsky, V; Kambara, M; Cardwell, D; Withignton, S; Jung, G (2002)
Microwave transmission through HTSC circular waveguides close to the cutoff conditions has been investigated. Applicative consequences of a sharp decrease in the transmitted power observed in the vicinity of the superconducting transition are discussed. (C) 2002 Elsevier Science B.V. All rights reserved.